2022
DOI: 10.21203/rs.3.rs-2118023/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A geochemical approach in assessing seawater intrusion by integrating geospatial techniques: a case study of Ghiss-Nekor coastal aquifer, Central Rif of Morocco

Abstract: For effective coastal aquifers management, it is strongly required to effectively analyze seawater intrusion (SWI). This study used an integrated approach of hydrogeochemical, statistical, geological, and geospatial techniques to assess the extent of SWI in the Ghiss-Nekor aquifer by evaluating the physicochemical parameters of 52 groundwater samples. Two main groundwater facies were identified, Na-Cl (38%) and Ca-Mg-Cl-SO4 (62%). The correlation matrix and a principal component analysis (PCA) depicted that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(125 reference statements)
0
1
0
Order By: Relevance
“…Research in the same region has revealed an increase in chloride and sulfate levels. Samples from the Ghiss-Nekkor plain show that high chloride concentrations in wells near the coast suggest seawater intrusion, while untreated polluted discharges account for elevated chloride levels in areas distant from the marine intrusion threat [20]. Most samples from the Bou-Arega aquifer show signs of chloride enrichment, with lower Na/Cl ratios and higher Cl/Br ratios than seawater [19].…”
Section: Resultsmentioning
confidence: 99%
“…Research in the same region has revealed an increase in chloride and sulfate levels. Samples from the Ghiss-Nekkor plain show that high chloride concentrations in wells near the coast suggest seawater intrusion, while untreated polluted discharges account for elevated chloride levels in areas distant from the marine intrusion threat [20]. Most samples from the Bou-Arega aquifer show signs of chloride enrichment, with lower Na/Cl ratios and higher Cl/Br ratios than seawater [19].…”
Section: Resultsmentioning
confidence: 99%